Pharmaceutical Effluent Treatment Using Multi-effect Evaporator Process. (21st August 2022) - Periyannan, R.; Arun Prasad, J.; Arulmozhi, S.; Balaji, M.; Gopalan, A.; Banu Priya, N. R.; Shanthi, P.; Shanmugavadivel, G.; Anukarthika, B.; Santino David Ladu, Nyagong
Abstract : The disposal practices of pharmaceutical-generated pollutants have become a serious threat to mankind's health, safety, and environmental concerns. Pharmaceutically polluted effluents have been demonstrated as endocrine disruptors which mimic growth hormones when consumed at nG/L to mG/L concentrations. The production stages utilize both organic and inorganic compounds, which contribute to chemical oxygen demand (COD) and total dissolved solids (TDS) heavily. Conventional technologies have failed to accomplish zero liquid minimization. To achieve zero minimization, it is necessary to develop modernization techniques in effluent treatment streams. A novel technique to recover solids and organic matter removals as well as zero-liquid discharge (ZLD) flash mixer, stripping, and multi-effect evaporator (MEE) processes is employed. Flash mixing is a pre-treatment stage, and stripping enables solvent reclamation. The multi-effect evaporators involve heat transfer equipment mainly used for volume reduction and cutting down on waste handling costs. The multi-effect evaporator not only is able to eliminate pharmaceutical xenobiotics but also requires pre-treatments such as flash mixture and stripping column sections. Thus, this research emphasizes efficiently removing high total dissolved solids (HTDS) and high chemical oxygen demand (HCOD) from pharmaceutical effluent. The removal efficiency was found to be 85% for TDS and TSS, 93% for BOD, and 81% for COD, which is more than the conventional mode of treatment.